1981
DOI: 10.1007/bf01315166
|View full text |Cite
|
Sign up to set email alerts
|

An immunoelectron microscopic and immunofluorescent study on the antigenic relationship between the coronavirus-like agent, CV 777, and several coronaviruses

Abstract: A possible antigenic relationship between the porcine enteropathogenic coronavirus-like agent (CVLA) and 6 known coronaviruses was examined by immunoelectron microscopy (IEM) and by immunofluorescence (IF). CVLA did not show cross reactivity with infectious bronchitis virus, transmissible gastroenteritis virus (TGEV), canine coronavirus (CCV) hemagglutinating encephalomyelitis virus (HEV), neonatal calf diarrhea coronavirus (NCDCV) or feline infectious peritonitis virus (FIPV). Antigenic relationship was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
3

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 11 publications
1
57
3
Order By: Relevance
“…(Collins et al, 1982;Hasony & Macnaughton, 1981, 1982Schmidt & Kenny, 1981, 1982Yaseen & Johnson-Lussenburg, 1981). Studies on the antigenic relationships of coronaviruses present a complex pattern, but the data suggest that the family can be divided into four distinct groups, and these are shown in Table 2 (Gerna et al, 1981 ;Horzinek et al, 1982;Macnaughton, 1981;Maru & Sato, 1982;Pedersen et al, 1978;Pensaert et al, 1981;Reynolds et al, 1980;Schmidt & Kenny, 1981).…”
Section: Relationships Between Coronavirusesmentioning
confidence: 99%
“…(Collins et al, 1982;Hasony & Macnaughton, 1981, 1982Schmidt & Kenny, 1981, 1982Yaseen & Johnson-Lussenburg, 1981). Studies on the antigenic relationships of coronaviruses present a complex pattern, but the data suggest that the family can be divided into four distinct groups, and these are shown in Table 2 (Gerna et al, 1981 ;Horzinek et al, 1982;Macnaughton, 1981;Maru & Sato, 1982;Pedersen et al, 1978;Pensaert et al, 1981;Reynolds et al, 1980;Schmidt & Kenny, 1981).…”
Section: Relationships Between Coronavirusesmentioning
confidence: 99%
“…They have been assigned to three groups. Initially this was based on antigenic relationships (McKintosh et al ., 1969;Bradburne, 1970;Pensaert et al ., 1981), which were later largely supported by gene sequencing. Some 25 years ago it was suggested that TCoV was closely related to BCoV of Group 2 (Dea et al ., 1990).…”
Section: Coronaviruses: the Three Groupsmentioning
confidence: 99%
“…failed to detect any antigenic cross-reactivity between PEDV and other coronaviruses (Pensaert et al, 1981;Kusanagi et al, 1992). However, some cross-reactivity has been detected with feline infectious peritonitis virus (FIPV;Yaling et aL, 1988).…”
Section: Introductionmentioning
confidence: 99%